2016
DOI: 10.1177/0890117116674681
|View full text |Cite
|
Sign up to set email alerts
|

Work Site–Based Environmental Interventions to Reduce Sedentary Behavior: A Systematic Review

Abstract: Environmental work site interventions to reduce sedentary behavior show promise because work sites often have more control over environmental factors. Limitations of this intervention stream include inconsistent measurement of sedentary behavior, absence of theoretical frameworks to guide program development, and absence of long-term evaluation. Future studies should include clear reporting of intervention strategies and explicit operationalization of theoretical constructs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
39
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 49 publications
0
39
0
1
Order By: Relevance
“…Environmental changes in sedentary behaviour interventions in the workplace tend to focus on restructuring the physical environment (29,30). Typically, these interventions have provided equipment such as a sit-to-stand workstation, in combination with other behaviour change strategies (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Environmental changes in sedentary behaviour interventions in the workplace tend to focus on restructuring the physical environment (29,30). Typically, these interventions have provided equipment such as a sit-to-stand workstation, in combination with other behaviour change strategies (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…goal setting, motivational interviewing). Whilst these types of interventions have been effective in reducing sedentary time (29)(30)(31), these may not be appropriate in a flexible workplace where it may not be feasible to modify workstations across multiple locations, including employee residences.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the use of active workplaces is currently recommended (Buckley et al, 2015), although, there is a lack of evidence whether they have an impact on health (Neuhaus et al, 2014;Shrestha et al, 2018;Tew, Posso, Arundel, & McDaid, 2015). One important reason for this lack is the use of inconsistent and nonobjective SB measurements (Hutcheson, Piazza, & Knowlden, 2018;Stephenson, McDonough, Murphy, Nugent, & Mair, 2017). While medicine is very skilled in diagnosing the diseases, measuring the dose of SB is still in its infancy, and it is too early to establish evidence-based health recommendations on SB (Stamatakis et al, 2019;van Uffelen et al, 2010).…”
mentioning
confidence: 99%
“…Based on the results of this study, it is necessary to reduce SB for workers in their 50s, as they had the longest sedentary time per day, and for workers in their 40s, as they had the longest sedentary time during work hours. With respect to the correlation between sedentary time per day and occupation, many studies have reported that SB influences occupation in terms of the sedentary time during work hours and walking [6,14]. In general, desk workers or drivers spend most of their work hours seated, and it is difficult to reduce their sedentary time.…”
Section: Discussionmentioning
confidence: 99%